PREDILATION BALLOONING IN HIGH THROMBUS LADEN ST ELEVATION MYOCARDIAL INFARCTION IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY REVASCULARIZATION. - Muhammad Fahim Ul Hassan1 , Irfan Ali Khan2 , Umer Farooq3 , Syed Ahsan Akhtar4 , Nazeef Ullah5 , Abid ullah6., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: In some cases, thrombus fragments created during predilation ballooning may cause distal embolization leading to slow flow or no-reflow. OBJECTIVE: To investigate the occurrence of intraprocedural slow flow/no reflow following primary percutaneous coronary intervention in patients with significant thrombus load both with and without predilation ballooning for culprit lesion preparation. MATERIAL AND METHODS: This descriptive observational study was carried out at interventional cardiology unit Hayatabad Medical Complex Peshawar from January 2022 to December 20222. Total 250 patients were enrolled. Clinical practice recommendations for the management of STEMI were followed during the entirety of all main PCI operations. The thrombus grade was divided into G0 to G5 categories. High thrombus burden is classified as grade 4, which means that the complete vascular blockage has thrombus covering more than half of the artery diameter. RESULTS: Total 250 patients were included in the study. Age ranged between 35-75 years with a mean age of 55 years. There were 152(60%) male while 98(40%) females with a ratio of 1.6:1. Patient were divided into 2 group i.e. group A (149, 59.6%) patients & group B (101,40.4%) patients. Group A consists of patients in whom Predilation ballooning was performed while Group B patients underwent Dottering and direct stenting. CONCLUSION. In patients with a significant thrombus burden, predilation ballooning may be linked to an increased risk of intraprocedural slow flow / no reflow after primary per cutaneous coronary intervention